2022
DOI: 10.3389/fnmol.2022.838311
|View full text |Cite
|
Sign up to set email alerts
|

RIBEYE B-Domain Is Essential for RIBEYE A-Domain Stability and Assembly of Synaptic Ribbons

Abstract: Synaptic ribbons are presynaptic specializations that define eponymous ribbon synapses. Synaptic ribbons are largely composed of RIBEYE, a protein containing an N-terminal A-domain and a carboxyterminal B-domain that is identical with CtBP2, a NAD(H)-binding transcriptional co-repressor. Previously we showed that synaptic ribbons are completely absent in RIBEYE knockout mice in which the RIBEYE A-domain-encoding exon had been deleted, but CtBP2 is still made, demonstrating that the A-domain is required for syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…In Ribeye KI mice, the enzymatic B-domain was replaced with GCamP3 and flanked with loxP sites for Cre-dependent deletion. As reported recently [ 34 ], we discovered that substituting GCamP3 for the RIBEYE B-domain eliminated ribbons throughout the retina. From OMR assays, we found that eliminating retinal ribbons reduced temporal resolution and contrast sensitivity.…”
Section: Introductionsupporting
confidence: 75%
“…In Ribeye KI mice, the enzymatic B-domain was replaced with GCamP3 and flanked with loxP sites for Cre-dependent deletion. As reported recently [ 34 ], we discovered that substituting GCamP3 for the RIBEYE B-domain eliminated ribbons throughout the retina. From OMR assays, we found that eliminating retinal ribbons reduced temporal resolution and contrast sensitivity.…”
Section: Introductionsupporting
confidence: 75%
“…Secondary antibody dilutions and references are given in Table 2. Following several washes with PBS, sections were embedded in NPG antifade, as previously described [12,17,38,75,76]. Immunolabeled sections were analyzed by confocal microscopy with an A1R confocal microscope, see below.…”
Section: Immunohistochemistry Of 10 µM Thick Cryostat Sections Of Mou...mentioning
confidence: 99%
“…The RIBEYE protein is the major component of synaptic ribbons [12][13][14][15][16][17]. RIBEYE consists of two main domains, an amino-terminal A domain that is unique to RIBEYE, and a carboxyterminal B domain that is identical, except for the first 20 amino-terminal amino acids, with the transcriptional co-repressor CtBP2 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Visualization of cone synapses with PNA-Alexa568 and immunolabeling of PNAstained cone terminals was performed exactly as previously described [83]. For the immunolabeling, the rabbit polyclonal Arl13b (Proteintech) was used in a 1:50 dilution in blocking solution, containing 0.5% BSA in PBS.…”
Section: Immunostaining Of Pna-stained Cone Synapses On Cryostat Sect...mentioning
confidence: 99%
“…For the immunolabeling, the rabbit polyclonal Arl13b (Proteintech) was used in a 1:50 dilution in blocking solution, containing 0.5% BSA in PBS. PNA-Alexa568 was diluted 1:200 in blocking buffer, exactly as described [83].…”
Section: Immunostaining Of Pna-stained Cone Synapses On Cryostat Sect...mentioning
confidence: 99%